2019
DOI: 10.1021/acs.inorgchem.9b02431
|View full text |Cite
|
Sign up to set email alerts
|

1O2 Generating Luminescent Lanthanide Complexes with 1,8-Naphthalimide-Based Sensitizers

Abstract: Lanthanide ion (LnIII) complexes with two new 1,8-naphthalimide-based ligands, Nap-dpe and Nap-cbx, were isolated, and their photophysical properties were explored. Upon excitation at 335 nm, Nap-dpe and Nap-cbx sensitize visible and near-infrared emitting LnIII ions (LnIII = EuIII, NdIII, and YbIII) and generate singlet oxygen (1O2). The quantum yields of EuIII luminescence for [Eu­(Nap-cbx)3]3+ and [Eu­(Nap-dpe)3]3+ are 16.7% and 8.3%, respectively, with 1O2 generation efficiencies of 41% and 59%, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 97 publications
(176 reference statements)
2
18
0
Order By: Relevance
“…The push−pull chromophores NPI-PTZ4 and NPI-PTZ5 were synthesized by the Sonogashira cross coupling of 3,7-diethynyl-10-octyl-10H-phenothiazine 3 with two equivalents of 6-bromo-2-butyl-1H benzo[de]isoquinoline-1,3(2H)-dione 1, and of 3,7-diethynyl-10-octyl-10H-phenothiazine 5,5-dioxide 5 42 with two equivalents of 6bromo-2-(2-ethylhexyl)-1H-benzo[de]isoquinoline-1,3(2H)dione 4, in 63% and 58% yields, respectively. The chemical structures of the synthesized molecules were confirmed by 1 H and 13 C NMR, HRMS, and MALDI-TOF mass spectrometry techniques, and the products are readily soluble in common organic solvents (see the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The push−pull chromophores NPI-PTZ4 and NPI-PTZ5 were synthesized by the Sonogashira cross coupling of 3,7-diethynyl-10-octyl-10H-phenothiazine 3 with two equivalents of 6-bromo-2-butyl-1H benzo[de]isoquinoline-1,3(2H)-dione 1, and of 3,7-diethynyl-10-octyl-10H-phenothiazine 5,5-dioxide 5 42 with two equivalents of 6bromo-2-(2-ethylhexyl)-1H-benzo[de]isoquinoline-1,3(2H)dione 4, in 63% and 58% yields, respectively. The chemical structures of the synthesized molecules were confirmed by 1 H and 13 C NMR, HRMS, and MALDI-TOF mass spectrometry techniques, and the products are readily soluble in common organic solvents (see the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Perylenediimide (PDI), naphthalenediimide (NDI), and diketopyrrolopyrrole (DPP) have been largely used as electron-acceptor units in new materials for optoelectronic and biochemical technologies because of their excellent chemical, thermal, and photostability. However, compared to the PDI, NDI, and DPP analogues, 1,8-naphthalimide (NPI) derivatives show the same positive properties while being even more promising dyes, because they are less affected by aggregation issues. More recently, phenothiazine (PTZ) was often used as the active component in push–pull chromophores because of its strong electron-donating capability .…”
Section: Introductionmentioning
confidence: 99%
“…Combination of the effect of bromine substituents and coordination of the ligand with Gd 3+ led to a synergistic effect on the singlet oxygen generation efficiency of the resulting complex (φΔ = 0.8 in chloroform). [47][48][49][50][51] The resulting complex [GdL1] also displayed large 2PA cross-section (540 GM), and we showed that micellar suspensions of the latter in pluronic was efficient in generating cancer cell death under 2P-activation. 38 Based on this background, we designed two new original MRI/PDT theranostic agents, complexes [GdL2(H2O)] and [GdL3(H2O)] (CN = 9, q = 1), using either a tacn ligand featuring two PDT-antennas and one acetate pendant moiety or a pyclen one, with one PDT sensitiser and two acetate arms arranged in a dissymmetric manner (Figure 1b).…”
Section: Introductionmentioning
confidence: 87%
“…in the range 41−64%. These complexes are not water-soluble 32 and are thus not viable for imaging and therapy applications in biological systems. More recently, we described a family of oligothiophene-based sensitizers of Ln III emission, which show wavelength-dependent 1 O 2 generation 33,34 but are also not water-soluble.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Our group has described dually functional complexes with naphthalimide-containing antennae that sensitize visible- (Eu III ) and near-infrared (NIR)-emitting (Yb III , Nd III , and Er III ) ions in addition to generating 1 O 2 with in the range 41–64%. These complexes are not water-soluble and are thus not viable for imaging and therapy applications in biological systems. More recently, we described a family of oligothiophene-based sensitizers of Ln III emission, which show wavelength-dependent 1 O 2 generation , but are also not water-soluble.…”
Section: Introductionmentioning
confidence: 99%